2003
DOI: 10.1074/jbc.m305235200
|View full text |Cite
|
Sign up to set email alerts
|

Acquirement of Brown Fat Cell Features by Human White Adipocytes

Abstract: Obesity, i.e. an excess of white adipose tissue (WAT), predisposes to the development of type 2 diabetes and cardiovascular disease. Brown adipose tissue is present in rodents but not in adult humans. It expresses uncoupling protein 1 (UCP1) that allows dissipation of energy as heat. Peroxisome proliferator-activated receptor ␥ (PPAR␥) and PPAR␥ coactivator 1␣ (PGC-1␣) activate mouse UCP1 gene transcription. We show here that human PGC-1␣ induced the activation of the human UCP1 promoter by PPAR␥. Adenovirus-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
279
1
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(301 citation statements)
references
References 65 publications
14
279
1
7
Order By: Relevance
“…Previous studies found brown fat emergence in WAT coupled with enhanced whole-body energy expenditure, but these studies used non-dietary manipulations, including chronic exposure to cold, treatment with b3-adrenergic receptor agonists and forced WAT overexpression of key molecules of brown fat adipogenesis/function, such as PGC-1a, UCP1 or PRDM16. 12,14,18,20,[39][40][41][42] Brown fat adipogenesis has recently gained the interest of many research groups, as compelling evidence has been provided that brown fat exists not only in human neonates, as thought originally, but also in human adults where it likely protects against obesity, 2-8 through its superior capacity for burning fat (both stored and eaten) and energy dissipation. 9,43 Substantial progress in our understanding of brown fat adipogenesis has been made recently (Seale et al 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found brown fat emergence in WAT coupled with enhanced whole-body energy expenditure, but these studies used non-dietary manipulations, including chronic exposure to cold, treatment with b3-adrenergic receptor agonists and forced WAT overexpression of key molecules of brown fat adipogenesis/function, such as PGC-1a, UCP1 or PRDM16. 12,14,18,20,[39][40][41][42] Brown fat adipogenesis has recently gained the interest of many research groups, as compelling evidence has been provided that brown fat exists not only in human neonates, as thought originally, but also in human adults where it likely protects against obesity, 2-8 through its superior capacity for burning fat (both stored and eaten) and energy dissipation. 9,43 Substantial progress in our understanding of brown fat adipogenesis has been made recently (Seale et al 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…17 Adenoviral-mediated gene transfer has also been demonstrated in differentiated adipocytes in vitro 18 and following adipose tissue injection in vivo, with transgene expression persisting for approximately 2 weeks. [19][20][21][22] However, preadipocytes of either human or murine origin were not transduced unless either very high multiplicities were applied or the cells were modified to express the coxsackie-adenovirus receptor (CAR) normally lacking on the surface of preadipocytes. 22,23 In contrast, retroviral-mediated transduction is limited to replicating preadipocytes, while nondividing adipocytes are not infected.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] However, preadipocytes of either human or murine origin were not transduced unless either very high multiplicities were applied or the cells were modified to express the coxsackie-adenovirus receptor (CAR) normally lacking on the surface of preadipocytes. 22,23 In contrast, retroviral-mediated transduction is limited to replicating preadipocytes, while nondividing adipocytes are not infected. 24 After cell transduction, the HSV genome persists as an intranuclear episomal element, 25 eliminating risks related to insertional mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when studied under the conditions of the above treatments, AMPK in WAT and other tissues was found to be activated (Jelenik et al 2010;Kopecky et al 2009;Orci et al 2004;Ye et al 2006). Concerning the mechanism of energy expenditure induced by the treatments, mitochondrial uncoupling mediated by UCP1 in WAT adipocytes (Orci et al 2004;Tiraby et al 2003;Petrovic et al 2010;Collins et al 1997;Guerra et al 1998;Himms-Hagen et al 2000) could be involved in most of the cases. Further studies are required to learn more about the mechanisms underlying the induction of energy dissipating adipocytes in response to treatments inducing UCP1 in adipose tissue.…”
Section: Treatments Enhancing Energy Expenditurementioning
confidence: 97%
“…Thus, treatment using leptin (Orci et al 2004), PPARa agonists (Ribet et al 2010), adrenoreceptor agonists and lipolytic agents (Granneman et al 2003;Yehuda-Shnaidman et al 2010), dietary n-3 polyunsaturated fatty acids (Jelenik et al 2010;Kopecky et al 2009;Flachs et al 2005), and thiazolidinediones acting as specific agonists of PPARc [TZD; (Tiraby et al 2003;Wilson-Fritch et al 2004;Petrovic et al 2010)] resulted in reduced adiposity and metabolic disturbances related to obesity, observed mostly under the conditions of high-fat feeding in obesity-prone C57BL/6 mice. Importantly, lipid catabolism in WAT was always up-regulated, and in situ lipogenesis in WAT was suppressed (Orci et al 2004;Ribet et al 2010;Flachs et al 2005;Tiraby et al 2003;Wilson-Fritch et al 2004), suggesting activation of AMPK Genes Nutr (2012) 7:369-386 381 in response to decreased energy status in WAT. Indeed, when studied under the conditions of the above treatments, AMPK in WAT and other tissues was found to be activated (Jelenik et al 2010;Kopecky et al 2009;Orci et al 2004;Ye et al 2006).…”
Section: Treatments Enhancing Energy Expenditurementioning
confidence: 99%